EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN POWTOON DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SDN GUNGGUNG I - Moh. Naofan Nafis; Ach. Royatus shidq; Nurrahman; Fajrul Falah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Student learning motivation varies between individuals. Students with high learning motivation tend to have a more in-depth learning experience compared to students with low motivation. When the majority of students have low motivation, the learning process often feels monotonous, boring, and can even cause students to lose enthusiasm and become sleepy. On the other hand, if most students have high learning motivation, the learning process becomes more lively, dynamic, and effective. Therefore, this study aims to analyze the effectiveness of using Powtoon as a learning media to improve the learning motivation of fourth-grade students. The method used in this journal is quantitative, and to strengthen the research, it is also supported by literature studies where the research results are taken from several references, such as articles, journals, and other research findings. The results of the study show that the use of Powtoon as a learning media significantly improves the learning motivation of fourth-grade students at SDN Gunggung I